Ammonothermal Synthesis of Novel Nitrides: Case Study on CaGaSiN3. Issue 11 (22nd December 2016) - Häusler, Jonas; Neudert, Lukas; Mallmann, Mathias; Niklaus, Robin; Kimmel, Anna‐Carina L.; Alt, Nicolas S. A.; Schlücker, Eberhard; Oeckler, Oliver; Schnick, Wolfgang
Abstract: The first gallium‐containing nitridosilicate CaGaSiN3 was synthesized in newly developed high‐pressure autoclaves using supercritical ammonia as solvent and nitriding agent. The reaction was conducted in an ammonobasic environment starting from intermetallic CaGaSi with NaN3 as a mineralizer. At 770 K, intermediate compounds were obtained, which were subsequently converted to the crystalline nitride at temperatures up to 1070 K (70–150 MPa). The impact of other mineralizers (e.g., LiN3, KN3, and CsN3 ) on the product formation was investigated as well. The crystal structure of CaGaSiN3 was analyzed by powder X‐ray diffraction and refined by the Rietveld method. The structural results were further corroborated by transmission electron microscopy, 29 Si MAS‐NMR, and first‐principle DFT calculations. CaGaSiN3 crystallizes in the orthorhombic space group Cmc 21 (no. 36) with lattice parameters a =9.8855(11), b =5.6595(1), c =5.0810(1) Å, ( Z =4, R wp =0.0326), and is isostructural with CaAlSiN3 (CASN). Eu 2+ doped samples exhibit red luminescence with an emission maximum of 620 nm and FWHM of 90 nm. Thus, CaGaSiN3 :Eu 2+ also represents an interesting candidate as a red‐emitting material in phosphor‐converted light‐emitting diodes (pc‐LEDs). In addition to the already known substitution of alkaline‐earth metals in (Ca, Sr)AlSiN3 :Eu 2+, inclusion of Ga is a further and promising perspective for luminescence tuning of widely used red‐emitting CASN type materials. Abstract : High‐pressure ammonolysis : The novel nitridogallosilicate CaGaSiN3 :Eu 2+ was synthesized as a new variant of CASN‐type materials by the ammonothermal method and features promising luminescence properties for the application in phosphor‐converted LEDs.